Identification of a Pain-Specific Gene Expression Profile for Pediatric Recurrent Abdominal Pain - Willits, Adam B.; Grossi, Victoria; Glidden, Nicole C.; Hyams, Jeffrey S.; Young, Erin E. (Frontiers in Pain Research, 2021)
Objectives: Functional Abdominal Pain (FAP) and Irritable Bowel Syndrome (IBS) are common recurrent abdominal pain diagnoses with the hallmark, lack of inflammation. To identify a biological signature for IBS/FAP in the colon, this study used genetic profiling to uncover gene expression changes associated with IBS/FAP and abdominal pain. Methods: Patients (8 to 17 years) newly diagnosed with IBS or FAP were enrolled in the study. At diagnostic colonoscopy, three rectal biopsies were collected, and gene expression analysis was performed using a Qiagen PCR Array. Relative fold difference in gene expression for 84 pain-associated genes was calculated using the 2-ΔΔ Cq method compared with pain-free controls. Factors affecting pain burden (Pain Burden Interview; PBI) were analyzed, including age, sex, rectal inflammation, and gene expression. Data were analyzed using multiple stepwise linear regression and 2-tailed t tests (P ≤ 0.05). Results: Of the 22 total patients in the study, 19 were diagnosed with either IBS-Constipation (frequency of 5.26%), IBS-Diarrhea (47.37%), IBS-Mixed (10.53%), or FAP (36.84%). IBS/FAP patients reported significantly higher pain burden at the time of diagnosis compared to pain-free controls (p < 0.001), as well as significantly higher abdominal pain (p = 0.01). Of the 84 genes, expression of GRIN1 (p = 0.02), MAPK3 (p = 0.04), P2X4 (p = 0.04), and PTGES3 (p = 0.02) were all significantly associated with PBI score. Discussion: Abdominal pain associated with IBS/FAP in pediatric patients may be linked to the expression of GRIN1, MAPK3, P2X4, and PTGES3, pointing to potential novel therapeutic targets for management of recurring abdominal pain.